Psychoanalytic reflections on the concept of moral autonomy starting from listening to mafia prisoners - Alparone, Dario (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Both for applicative purposes, especially in the legal-forensic and criminological fields, and for theoretical purposes, the psychoanalytic investigation of the notion of autonomy can be of very current interest for the philosopher who deals with law. The issue of subjective autonomy arises in psychoanalysis in terms of the construction process, and as such it can have important theoretical repercussions for the philosopher in order to rethink the function of law and useful to the jurist to understand crime in a different light . Parole chiave: Psychoanalysis; Moral Philosophy; Mafia; Acknowledgment; Criminology Indice: 1. Introduzione – 2. L’autonomia individuale come processo sociale – 3. Il riconoscimento e l’Altro simbolico della legge – 4. L’atto criminale e la fantasia inconscia – 5. Il sogno di S. e la Legge della pulsione – 6. L’ordine criminale – Riferimenti bibliografici